Observation of spin Seebeck contribution to the transverse thermopower in Ni-Pt and MnBi-Au bulk nanocomposites - Stephen R. Boona (Nature Portfolio, 2016)
The spin Seebeck effect enables thermal-to-electrical energy conversion but the power generated in thin films remains low. Here, Boonaet al. use composites of ferromagnetic conductors containing noble metal nanoparticles to show that the effect can enhance the transverse thermopower of bulk materials.